Fundamentals of Innovative Aircraft Heat Exchanger Integration for Hydrogen–Electric Propulsion - Bernhard Gerl; Matthias Ronovsky-Bodisch; Niccoló Ferrari; Martin Berens (Aerospace)
The potential of utilizing the rejected heat of a fuel cell system to improve the aircraft propulsive efficiency is discussed for various flight conditions. The thermodynamic background of the process and the connection of power consumption in the fan of the ducted propulsor and fuel cell heat are given, and a link between these two components is presented. A concept that goes beyond the known ram heat exchanger is discussed, which outlines the potential benefits of integrating a fan upstream of the heat exchanger. The influence of the fan pressure ratio, flight speed, and altitude, as well as the temperature level of the available fuel cell heat on the propulsive efficiency, is presented. A correlation between the fan pressure ratio, flight speed, and exchangeable fuel cell heat is established, providing a simplified computational approach for evaluating feasible operating conditions within this process. This paper identifies the challenges of heat exchanger integration at International Standard Atmosphere sea level conditions and its benefits for cruise flight conditions. The results show that for a flight Mach number of 0.8 and a fan pressure ratio of 1.5 at a cruising altitude of 11,000 m, the propulsion efficiency increases by approximately 8 percentage points compared to a ducted propulsor without heat utilization. Under sea-level conditions, the concept does not offer any performance advantages over a ducted propulsor. Instead, it exhibits either comparable or reduced propulsive efficiency.